Interstitial fluid as a proxy of glymphatic dysfunction in patients with cognitive impairment: The necessity of three‐directional intravoxel incoherent motion. Issue 4 (1st February 2022) - Thiel, Merel M.; Freeze, Whitney M.; Jong, Joost J.; Ramakers, Inez H.G.B.; Backes, Walter H.; Jansen, Jacobus F.A.
Abstract: Background: IntraVoxel Incoherent Motion (IVIM) MRI can detect an intermediate diffusion component, which is thought to be related to increased interstitial fluid (ISF). However, IVIM imaging with a proper estimation of the diffusion tensor requires a long acquisition time (∼10 min), which is not feasible in clinical practice. This study simultaneously examines the contribution of individual diffusion directions and the potential group differences between patients with Alzheimer's disease (AD), mild cognitive impairment (MCI), and cognitively normal controls (CN). We foresee to find a higher ISF‐fraction in patients compared with controls, as underlying pathologic processes, e.g. inflammation and oedema, would ultimately lead to loss of tissue structure and increase in ISF. Method: Patients with AD dementia (n=15) and MCI (n=15), and 33 CNs underwent 3T MRI. IVIM images were acquired with a range of b ‐values (10‐1000 s/mm 2 ) in three orthogonal diffusion directions: M (left‐right), P (anterior‐posterior) and S (superior‐inferior) (Fig. 1). The intermediate diffusion components ( Dint ) in the range 1.5<Diffusivity<4.0*10 ‐3 mm2/s, for each direction and average (trace) diffusion images were calculated with spectral analysis and the relative signal contribution of Dint was quantified by the ISF‐fraction ( fint ). The median values of the parenchymal diffusivity ( Dpar ), Dint and fint were extracted from the normal appearing white matter and corpus callosum. Per brain region, the fint, Dpar and Dint values were compared between the subject groups using multivariate linear regression while correcting for age and sex. Result: Group characteristics and descriptive statistics are shown in Table 1 and 2. Table 3 contains all significant group differences of fint, Dpar, and Dint, derived by the M, P, S and trace images, which shows a higher fint in patients than in CNs. Similar group differences in fint can be obtained from the M‐direction and the trace (Fig. 2) Conclusion: A higher ISF‐fraction was found in AD patients as compared to CNs, which is expected to point out tissue degeneration. The ISF‐fraction assessed with spectral analysis in IVIM can be considered as a potential non‐invasive biomarker related to glymphatic alterations in brain disease. As the M‐direction was sufficiently sensitive to determine differences in ISF fraction, more clinically acceptable acquisition times can be achieved.